2022
DOI: 10.1063/5.0088526
|View full text |Cite
|
Sign up to set email alerts
|

Protein conformational changes and protonation dynamics probed by a single shot using quantum-cascade-laser-based IR spectroscopy

Abstract: Mid-IR spectroscopy is a powerful and label-free technique to investigate protein reactions. In this study, we use quantum-cascade-laser-based dual-comb spectroscopy to probe protein conformational changes and protonation events by a single-shot experiment. By using a well-characterized membrane protein, bacteriorhodopsin, we provide a comparison between dual-comb spectroscopy and our homebuilt tunable quantum cascade laser (QCL)-based scanning spectrometer as tools to monitor irreversible reactions with high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Thermal back-isomerization of the chromophore occurs during the N–O transition, and deprotonation of the Asp sidechain completes the catalytic cycle . Most transient IR studies have been performed with “slower” spectroscopic techniques, such as step-scan FTIR spectroscopy ,,,,, or more recently with the help of quantum cascade lasers while the fs–ps timescale has been addressed separately. , …”
Section: Resultsmentioning
confidence: 99%
“…Thermal back-isomerization of the chromophore occurs during the N–O transition, and deprotonation of the Asp sidechain completes the catalytic cycle . Most transient IR studies have been performed with “slower” spectroscopic techniques, such as step-scan FTIR spectroscopy ,,,,, or more recently with the help of quantum cascade lasers while the fs–ps timescale has been addressed separately. , …”
Section: Resultsmentioning
confidence: 99%
“…An emerging transient absorption technique using quantum cascade laser (QCL) has been employed in the spectral and kinetic investigations of reactive species in gaseous phase, summarized by Chung and Lee [132]. QCL-based transient absorption has also been employed in probing the photocycle of bacteriorhodopsin in condensed phase [133,134]. An absorbance difference as low as 1 Â 10 À4 is achievable in single-shot QCL experiments at t > 1 μs [133].…”
Section: Discussionmentioning
confidence: 99%
“…It can be countered that the [Ser/Thr] K+1 –Asp WB pair does not interact directly with W cat . However, direct tracing of intra-protein displacements of protons in energy converting enzymes and chemical models (see [ 181 , 182 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 ] for reviews) showed that fast proton transfer over a distance of up to 20 Å can be mediated by water bridges, provided that the distance between the groups involved is ≤3.0 Å, in accordance with Eigen [ 182 ]. Thereby it does not matter that water molecules are equally poor proton acceptors (with pK b of 0.0) and proton donors (with pK a of 14.0) because protons pass water by the so-called von Grotthuss mechanism [ 210 , 211 , 212 ].…”
Section: Discussionmentioning
confidence: 99%